The Effect of X-Ray Radiation to IL-10 Levels in Secretome Mesenchymal Stem Cells Cosmeceutical Product - Antari, Arini Dewi; Ghaissani, Shabrina Syifa; Prawitasari, Salindri; Haryono, Erlina; Adityani, Resanti (International Journal of Cell and Biomedical Science, 2023)
Background: X-ray radiation has been widely used in the pharmaceutical industry because it regenerates and repairs damaged tissues. Objective: In this study, we evaluate the effect of X-ray radiation on the secretome cosmeutical product. Methods: We conducted interleukin 10 (IL-10) analysis by ELISA in each product sample after exposure to X-ray radiation. Results: The levels of IL-10 in each sample were significantly lower than those in the control samples. Moreover, the level of IL-10 in the product samples was significantly higher than that of the control sample. Conclusion: In conclusion, exposure to radiation during shipping or storage of skin care products can potentially damage the proteins in the products by inducing the production of reactive oxygen species (ROS) and decreasing the treatment effectiveness.